Welding electrode for petrochemical low-temperature storage tank
By using a combination of ultra-low carbon low alloy welding core and high potassium, high alkalinity and low hydrogen slag-based medicine skin, we ensure that the weld has high strength and high impact toughness after long-term heat treatment, solving the problems of existing welding rods decreasing toughness and metal strength at low temperatures.
Patent Information
- Application Number
- CN202411937589.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing welding rods matching 3.5% Ni steel have reduced toughness at low temperatures, the metal strength is difficult to meet the standard requirements, and the weld strength is difficult to maintain under long-term heat treatment conditions.
The welding rod for petrochemical low-temperature storage tanks composed of welding cores and powder skins is used. The welding core is composed of ultra-low carbon and low alloys. The powder skin contains high potassium, high alkalinity, low hydrogen slag systems and multiple fluorides. Through precise ratio and heat treatment technology, weld metals have high strength and high impact toughness after long-term heat treatment.
The strength of the weld metal meets the standard requirements after a long heat treatment of 620℃×6-14h, and the impact value at -101℃ reaches more than 120J, solving the problems of lower low-temperature toughness and lower metal strength.
Smart Images

Figure BDA0005211877410000091 
Figure BDA0005211877410000092 
Figure BDA0005211877410000101
Abstract
Description
Technical Field
[0001] The invention belongs to the field of welding materials, and particularly relates to an electric welding rod for a petrochemical low-temperature storage tank. Background Art
[0002] Since the late 1980s, my country has listed special research and development projects for low-temperature steel and its application technology with the goal of localizing low-temperature equipment in large-scale ethylene, synthetic ammonia and city gas devices, among which the application of 3.5% Ni steel is the preferred key project. 3.5% Ni steel is one of the Ni-containing low-temperature steels. Its minimum operating temperature can generally reach -101℃ (the minimum operating temperature of the quenched and tempered state can reach -120℃), and it is widely used in the manufacture of -80~-101℃ petrochemical low-temperature equipment.
[0003] 3.5% Ni steel is mainly used to make oil and air separation oxygen production equipment and synthetic ammonia and other container equipment. With the development of the petrochemical industry, petrochemical storage tanks are developing towards large-scale, and the thickness of steel plates is also increasing. my country's demand for this steel is increasing. Wuyang Iron and Steel Company has been developing 3.5% Ni steel plates since 2007, and has achieved domestic production to replace imports for the construction of major national projects. It is very necessary to develop welding materials with various performance indicators close to the level of similar foreign products, and which can adapt to large storage tanks, thick plates, large line energy, high efficiency and long-term heat treatment. It has important practical significance and significant economic benefits for realizing the localization of 3.5% Ni steel welding materials and promoting the development of the national welding materials industry, and promoting the wider application of 3.5% Ni steel in my country's petrochemical industry.
[0004] The welding materials currently used are still largely imported. The welding rods matched with 3.5% Ni steel in the existing technology often have the following disadvantages: when the welding current or heat input is too large, the low-temperature toughness of the weld metal at -101℃ is significantly reduced; in addition, in order to ensure the impact toughness at -101℃, the strength design of the welding materials on the market is generally based on the principle of equal strength or low strength matching. With the increase in the volume of storage tanks, the thickness of steel plates increases, requiring the heat treatment time of welding materials to increase synchronously. As the heat treatment time increases, the strength of the weld metal decreases. Under long-term heat treatment conditions, the weld strength is difficult to meet the standard requirements. If the strength of the welding rod is simply increased, its -101℃ impact toughness will be significantly deteriorated. Summary of the invention
[0005] In order to solve the deficiencies of the prior art, the present invention provides a welding rod for petrochemical low-temperature storage tanks, the strength of the deposited metal after long-term heat treatment at 620℃×6-14h can meet the standard requirements, and the -101℃ impact value can reach more than 120J, which solves the defects of the welding rods matched with 3.5% Ni steel in the prior art, such as the decrease in low-temperature toughness and the decrease in metal strength. The welding rod of the present invention also has good welding process characteristics such as stable and soft arc, high deposition efficiency, good all-position weldability, uniform slag coverage, easy slag removal, and beautiful weld formation; the developed welding rod has wide adaptability, can be used for AC and DC welding, and can meet the welding needs of large-scale, large line energy, and high efficiency.
[0006] The technical solution of the present invention is an electric welding rod for petrochemical low-temperature storage tanks, which is composed of a welding core and a coating, and the coating is coated on the outer wall of the welding core; based on the total weight of the welding core, according to weight percentage, the components of the welding core are as follows: C≤0.020%, Si≤0.10%, Mn: 0.35-0.60%, P≤0.005%, S≤0.008%, P+S≤0.012%, Ni: 3.0-3.75%, Fe: balance;
[0007] Based on the total weight of the coating, the components of the coating are as follows in terms of weight percentage: magnesite: 5-12%, calcite: 24-32%, barium carbonate: 2-4%, fluorite: 12-18%, barium fluoride: 3.0-5.0%, lithium fluoride: 1.0-3.0%, cerium fluoride: 0.4-1.2%, silicon micropowder: 3-10%, zircon sand: 0.6-2.5%, potassium cryolite: 1.0-3.0%, potassium glass powder: 0. 5-2.0%, low nitrogen nickel powder (N≤0.005%): 2.6-3.4%, low nitrogen molybdenum powder (N≤0.005%): 0.15-0.18%, manganese silicon alloy: 3-6%, ferroboron (B content 18-20%): 0.1-0.3%, magnesium powder: 0.5-1.2%, calcium alginate: 0.8-1.2%, potassium alginate: 0.4-0.6%, low titanium atomized iron powder (Ti≤0.005%): balance.
[0008] Potassium-sodium mixed water glass with a modulus of 3.30 and a concentration of 35±1Be, which accounts for 15-30% of the total weight of the coating, is added, mixed with the coating, and evenly coated on the welding core, and then dried at a low temperature of 80-120°C for 3 hours and a high temperature of 350-420°C for 1 hour to prepare the petrochemical low-temperature storage tank welding rod.
[0009] In terms of weight percentage, the chemical composition of the deposited metal of the welding rod for petrochemical low-temperature storage tanks is as follows: C: 0.020-0.040%, Si: 0.15-0.25%, Mn: 0.50-0.80%, P: ≤0.008%, S: ≤0.008%, P+S≤0.015%, Ni: 3.30-3.70%, Mo: 0.06-0.08%, B: 0.0012-0.0018%, Mo / B=30-60, Ti: ≤0.001%, and the rest is Fe.
[0010] Preferably, the composition of the welding core is as follows: 0.010≤C≤0.020%; Si≤0.10%; Mn: 0.35-0.60%; P: ≤0.005%; S: ≤0.005%; P+S≤0.010%; Ni: 3.20-3.75%, Fe: balance.
[0011] Preferably, the components of the coating are as follows: magnesite: 6-10%; calcite: 26-30%; barium carbonate: 2.5-4.0%; fluorite: 14-16%; barium fluoride: 3.5-4.8%; lithium fluoride: 1.6-2.4%; cerium fluoride: 0.6-1.0%; silicon micropowder: 6-9%; zircon sand: 0.6-1.8%; potassium cryolite: 1.6-3.0%; potassium glass powder: 1.0-2.0%; low nitrogen Nickel powder (N≤0.005%): 2.8-3.2%; low nitrogen molybdenum powder (N≤0.005%): 0.15-0.18%; manganese silicon alloy: 4.2-5.8%; ferroboron (B: 18-20%): 0.15-0.30%; magnesium powder: 0.75-1.20%; calcium alginate: 0.8-1.2%; potassium alginate: 0.4-0.6%; low titanium atomized iron powder (Ti≤0.005%): balance.
[0012] Preferably, the silicon powder in the coating component is micron-grade, extremely fine in particle size, and can pass through 500 mesh; the particle size of potassium glass powder is 250-300 mesh; and the particle size of calcium alginate and potassium alginate is 150-200 mesh.
[0013] Preferably, in terms of weight percentage, the chemical composition of the deposited metal of the welding rod for petrochemical cryogenic storage tanks is controlled within the range of: C: 0.024-0.036%, Si: 0.15-0.22%, Mn: 0.58-0.72%, P: ≤0.006%, S: ≤0.006%, P+S≤0.012%, Ni: 3.45-3.65%, Mo: 0.06-0.08%, B: 0.0012-0.0018%, Mo / B=36-54, Ti: ≤0.001%, and the remainder is Fe.
[0014] Preferably, as a preferred embodiment of the electric welding rod for petrochemical low-temperature storage tanks of the present invention, the welding core composition is as follows: C: 0.013%; Si: 0.03%; Mn: 0.42%; P: 0.003%; S: 0.005%; P+S: 0.008%; Ni: 3.27%, Fe: balance; the coating composition is as follows: magnesite: 7.4%; calcite: 26.0%; barium carbonate: 2.6%; fluorite: 15.0%; barium fluoride: 4.2%; lithium fluoride: 2.4% ; Cerium fluoride: 1.0%; Silica powder: 6.0%; Zirconium sand: 1.7%; Potassium cryolite: 1.6%; Potassium glass powder: 1.1%; Low nitrogen nickel powder (N≤0.005%): 2.9%; Low nitrogen molybdenum powder (N≤0.005%): 0.15%; Manganese silicon alloy: 4.25%; Ferroboron (B: 18-20%): 0.15%; Magnesium powder: 0.85%; Calcium alginate: 0.90%; Potassium alginate: 0.40%; Low titanium atomized iron powder (Ti≤0.005%): balance.
[0015] Preferably, as another preferred embodiment of the electric welding rod for petrochemical cryogenic storage tanks of the present invention, the welding core composition is as follows: C: 0.017%; Si: 0.04%; Mn: 0.35%; P: 0.005%; S: 0.005%; P+S: 0.010%; Ni: 3.44%, Fe: balance; the coating composition is as follows: magnesite: 10.0%; calcite: 30.0%; barium carbonate: 2.8%; fluorite: 14.0%; barium fluoride: 4.0%; lithium fluoride: 1.6 %; cerium fluoride: 0.8%; silicon powder: 6.7%; zircon sand: 1.0%; potassium cryolite: 2.4%; potassium glass powder: 1.6%; low nitrogen nickel powder (N≤0.005%): 2.8%; low nitrogen molybdenum powder (N≤0.005%): 0.18%; manganese silicon alloy: 5.00%; ferroboron (B: 18-20%): 0.25%; magnesium powder: 1.00%; calcium alginate: 1.10%; potassium alginate: 0.55%; low titanium atomized iron powder (Ti≤0.005%): balance.
[0016] Preferably, as another preferred embodiment of the electric welding rod for petrochemical cryogenic storage tanks of the present invention, the welding core components are as follows: C: 0.011%; Si: 0.04%; Mn: 0.47%; P: 0.004%; S: 0.003%; P+S: 0.007%; Ni: 3.75%, Fe: balance; the coating components are as follows: magnesite: 9.7%; calcite: 28.0%; barium carbonate: 4.0%; fluorite: 16.0%; barium fluoride: 3.6%; lithium fluoride: 1.8 %; cerium fluoride: 0.7%; silicon powder: 8.0%; zircon sand: 0.6%; potassium cryolite: 3.0%; potassium glass powder: 2.0%; low nitrogen nickel powder (N≤0.005%): 3.1%; low nitrogen molybdenum powder (N≤0.005%): 0.17%; manganese silicon alloy: 5.40%; ferroboron (B: 18-20%): 0.30%; magnesium powder: 1.20%; calcium alginate: 1.20%; potassium alginate: 0.60%; low titanium atomized iron powder (Ti≤0.005%): balance.
[0017] The beneficial effects of the present invention based on its technical solution are:
[0018] The present invention is an ultra-low carbon low alloy welding core, the main alloy elements are transitioned from the welding core, and the ultra-low P and S component design is a prerequisite for ensuring that the weld metal has excellent crack resistance and high toughness.
[0019] The formation of carbides during welding will significantly reduce the impact toughness of the weld, especially the low-temperature impact at -101°C. In order to ensure good -101°C impact toughness, the present invention is designed as a high-basicity, high-potassium, low-hydrogen slag system. As we all know, the higher the basicity, the higher the C increase of the weld relative to the weld core. In order to ensure a lower C content level in the weld, an ultra-low carbon, low-alloy weld core is designed. Through precise proportioning of the coating and reasonable optimization of the composition and proportion of alloy elements, the resulting weld metal has better chemical stability, and better -101°C impact stability under long-term heat treatment and high heat input welding conditions.
[0020] The present invention adopts a high potassium, high basicity, low hydrogen slag system, with good arc stability and capable of AC and DC welding. The addition of polyfluorides in different proportions has a stronger dehydrogenation ability, and the high proportion of carbonate compositions with different decomposition temperatures can increase the CO2 partial pressure in the arc atmosphere during the entire welding process, reduce the hydrogen partial pressure, and do not add silicate minerals with high crystal water content, and the level of diffused hydrogen is low. The polycarbonate and fluoride ratios are precisely designed, the coating melts evenly, the arc stiffness is good, and the weldability in all positions is excellent.
[0021] The invention is designed to add micron-grade silicon powder and potassium glass powder with a particle size of 200-300 meshes, so that the electrode coating can be smoother and the density of the electrode coating can be improved, and the moisture-proof ability is better.
[0022] The present invention adopts an alloy system of low C-medium Mn-low Si-3.5% Ni-containing Mo and B. High Ni, low C and low Si are the basic guarantees for -101°C impact toughness. Microalloying of a small amount of Mo and a trace amount of B is the key to maintaining the strength of the weld during long-term heat treatment. Ti-free is the core of the stability of -101°C impact toughness under long-term heat treatment and high-energy input welding conditions. A small amount of Mo and a trace amount of B can refine the grains, improve the impact toughness of the weld while strengthening it, and it is appropriate to control the Mo / B ratio in the range of 30-60, and 36-54 is the best.
[0023] The electrode coating in the present invention mainly functions to stabilize the arc, generate gas, form slag, deoxidize and transfer a small amount of alloy to the weld.
[0024] The specific analysis of the main components of the medicine coating and the alloy in the welding rod of the present invention is as follows:
[0025] The main functions of carbonates in welding rods are slag formation and gasification, and they have the function of removing sulfur, which can improve the crack resistance of weld metal. The alkaline oxides such as CaO and MgO produced by decomposition can increase the basicity of slag, and also have the function of adjusting the melting point, viscosity and surface tension of slag. The present invention adopts a polybasic carbonate composition, and a high proportion of carbonate compositions with different decomposition temperatures can increase the CO2 partial pressure in the arc atmosphere during the entire welding process, reduce the hydrogen partial pressure, and reduce the low level of hydrogen diffusion in the welding material. The ratio of polybasic carbonates and fluorides is precisely designed, the coating melts evenly, the arc stiffness is good, and the weldability in all positions is excellent. The carbonate content of the present invention is controlled at 31-48%;
[0026] The present invention adopts a combination of multi-element fluorides, which are fluorite (CaF2), barium fluoride, lithium fluoride and cerium fluoride. It can adjust the melting point of the slag, reduce the surface tension of the liquid metal, and play a key role in reducing the diffused hydrogen content of the weld, improving weld formation, slag removal, etc. A large number of orthogonal test practices have shown that the combination of fluorite, barium fluoride and lithium fluoride makes the dehydrogenation ability of the coating particularly outstanding. In addition, in addition to transitioning rare earth elements to the weld, cerium fluoride also has the functions of dehydrogenation, deoxidation, purification and impurity removal. The rare earth elements transitioning to the weld play a key role in refining the weld metal structure and improving the strength and toughness of the weld metal. However, because rare earths themselves are very expensive, adding too much will significantly increase the manufacturing cost. Therefore, the content of rare earth fluoride in the welding rod of the present invention is controlled at 0.4-1.2%;
[0027] Silicon oxide and aluminum oxide obtained from silicon powder, cryolite, potassium glass powder, water glass, etc. can adjust the viscosity of molten welding slag to make the welding slag cover better and improve the appearance and shape of the weld. However, when the proportion of silicon oxide is too high, the O content of the weld will be too high, thereby reducing the mechanical properties of the weld, especially the low-temperature impact toughness. It will also make it difficult to remove the slag from the weld, so the proportion of silicon oxide and aluminum oxide in the welding flux is controlled at a lower level;
[0028] The present invention adopts a Ti-free formula design. It is well known that the Ti element is widely used in low-temperature steel welding materials. It can deoxidize and refine grains. It can significantly improve the weld structure and improve low-temperature impact toughness when matched with boron in a suitable proportion. However, in 3.5% Ni steel welding materials, the Ti / B ratio is more difficult to control and the impact value is also extremely unstable, especially after long-term heat treatment. Therefore, traditional 3.5% Ni steel welding materials on the market mostly add Ti but no B. In order to meet the strength and impact toughness of the welding material after long-term heat treatment, the present invention adopts a Ti-free, low C-medium Mn-low Si-3.5% Ni-Mo and trace B alloy system. The present invention is designed to use titanium-free atomized iron powder, without adding raw materials such as titanium dioxide, rutile or titanium alloy.
[0029] The main functions of ferroalloy and other metal powders are deoxidation and transition alloying, ensuring the alloying element composition in the weld, ensuring the weld strength and achieving the best strength and toughness matching through reasonable element design. In particular, the present invention specifically controls the ratio of low-nitrogen molybdenum powder and ferroboron so that the Mo / B ratio of the deposited metal is controlled at 30-60 (preferably 36-54) to achieve the ideal comprehensive improvement effect of grain refinement, toughness improvement and crack resistance enhancement;
[0030] The binder is made of potassium sodium water glass with alginate with a particle size controlled at 100-200 mesh and extremely fine micron-sized silicon powder. The main functions of the binder are plasticization, viscosity increase, improvement of welding rod paintability and appearance, as well as slag formation and arc stabilization.
[0031] The above is the reason for limiting the composition of the coating component of the welding rod for petrochemical cryogenic storage tank of the present invention. The remaining part is iron and unavoidable impurities.
[0032] The welding rod of the present invention can well match the performance of 3.5% Ni steel plate, has high deposition efficiency, wide adaptability, and can be used for AC and DC welding. The strength of the deposited metal can meet the standard requirements after long-term heat treatment at 620℃×6-14h, and the impact value at -101℃ can reach more than 120J, and can meet the welding needs of large-scale, large-line energy, and high efficiency. In addition to high strength and high toughness, the deposited metal is butt-welded with 3.5% Ni steel parent material, and the tensile strength is ≥520MPa and the -101℃ impact is ≥70J after heat treatment at 620±20℃×6~14h. DETAILED DESCRIPTION
[0033] In order to better understand the present invention, the technical solutions of the present invention are further described below in conjunction with specific embodiments, but the present invention is not limited to these embodiments.
[0034] The invention discloses an electric welding rod for a petrochemical cryogenic storage tank, which is a high-quality ultra-low carbon low alloy welding core. A coating is applied to the outer wall of the welding core. According to weight percentage, the specific chemical composition (wt%) of the welding core is as follows: C≤0.020%, Si≤0.10%, Mn: 0.35-0.60%, P≤0.005%, S≤0.008%, P+S≤0.012%, Ni: 3.0-3.75%, and Fe: balance.
[0035] Based on the total weight of the coating, the components of the coating are as follows in terms of weight percentage: magnesite: 5-12%, calcite: 24-32%, barium carbonate: 2-4%, fluorite: 12-18%, barium fluoride: 3.0-5.0%, lithium fluoride: 1.0-3.0%, cerium fluoride: 0.4-1.2%, silicon micropowder: 3-10%, zircon sand: 0.6-2.5%, potassium cryolite: 1.0-3.0%, potassium glass powder: 0. 5-2.0%, low nitrogen nickel powder (N≤0.005%): 2.6-3.4%, low nitrogen molybdenum powder (N≤0.005%): 0.15-0.18%, manganese silicon alloy: 3-6%, ferroboron (B: 18-20%): 0.1-0.3%, magnesium powder: 0.5-1.2%, calcium alginate: 0.8-1.2%, potassium alginate: 0.4-0.6%, low titanium atomized iron powder (Ti≤0.005%): balance.
[0036] The total weight of the coating is 15-30%, the modulus is 3.30, and the concentration is 35±1Be. The coating flux is evenly coated on the welding core by a hydraulic coating machine; and the welding rod is dried at low temperature of 80-120°C for 3 hours and at high temperature of 350-420°C for 1 hour respectively.
[0037] The welding core of the present invention is a high-quality ultra-low carbon low alloy welding core. The specific contents in the embodiments are shown in Table 1 (Examples 1, 3 and 4 are preferred embodiments [with better low-temperature impact toughness], the same below).
[0038] Table 1: Examples of solder core compositions (weight %)
[0039]
[0040] The coating adopts high potassium, high basicity and low hydrogen slag system, the coating accounts for 0.50-0.62 of the total weight of the electrode, the core wire diameter is 3.2mm, 4.0mm, 5.0mm, and the coating component implementation example is shown in Table 2.
[0041] Table 2: Composition of the coating in each example (weight percentage %)
[0042]
[0043] Table 2: Composition of the coating in each example (weight percentage)
[0044]
[0045] Table 3: Chemical composition of deposited metal in various embodiments (weight percentage %)
[0046]
[0047] The test results of the mechanical properties of the deposited metals in each embodiment are shown in Tables 4-1 and 4-2:
[0048] Table 4-1: Test results of deposited metal properties of various embodiments (DC)
[0049]
[0050] Note: The above test data are: welding material specification Φ4.0mm, heat treatment conditions 620±20℃×6h, heat input 10-15KJ / cm;
[0051] Table 4-2: Test results of deposited metal properties of various embodiments (AC)
[0052]
[0053] Note: The above test data are: welding material specification Φ4.0mm, heat treatment conditions 620±20℃×6h, heat input 10-15KJ / cm;
[0054] Taking Example 4 as an example, different heat treatment times and different heat inputs were tested, and the results are shown in Tables 5 to 9.
[0055] Table 5 Properties of deposited metal under different heat treatment times
[0056]
[0057] Table 6: Deposited metal properties at different heat inputs
[0058]
[0059] Table 7: Deposited metal properties at different heat inputs
[0060]
[0061] Table 8: Vertical welding joint performance under different heat input
[0062]
[0063] Table 9: Vertical welding joint performance under different heat input
[0064]
[0065] It can be seen from the experimental results in Tables 5 to 9 that the deposited metal of the welding rod of the present invention has excellent performance, low diffusible hydrogen content, and excellent low-temperature impact toughness of -101°C under different heat input conditions and after heat treatment at 620°C×6~14h. When butt-welded with 3.5% Ni steel base material, within the range of 35KJ / cm heat input, after heat treatment at 620°C×6~14h, the tensile strength is ≥490MPa (which can meet the requirements of relevant standards), the impact at -101°C is ≥70J, and there are no cracks in face bending, back bending and lateral bending, and the crack resistance is excellent.
[0066] The welding rod of the present invention is suitable for welding of 3.5% Ni steel petrochemical low-temperature storage tanks. The welding material has wide adaptability, can be used for AC and DC welding, can withstand long-term heat treatment (can withstand 620±20℃×6~14h heat treatment), and can be welded with large heat input (can be applied to 35KJ / cm). Under the heat treatment conditions of 620±20℃×6~14h, the deposited metal has high impact toughness at -101℃ (-101℃≥120J). It solves the defects of reduced low-temperature toughness and reduced metal strength that are common in welding rods matching 3.5% Ni steel in the prior art. The welding rod of the present invention has excellent all-position welding process performance and high deposition efficiency. It can meet the welding requirements of large thick plates, large heat input and high efficiency caused by the increasing size of storage tanks.
[0067] The above-described embodiments are only preferred implementations of the present invention. It should be pointed out that a person skilled in the art may make several modifications and improvements without departing from the inventive concept of the present invention, and these modifications and improvements all belong to the protection scope of the present invention.
Claims
1. A welding rod for a petrochemical low-temperature storage tank, comprising a welding core and a coating, wherein the coating is applied to the outer wall of the welding core, characterized in that: Based on the total weight of the welding core, the components of the welding core are as follows in terms of weight percentage: C≤0.020%, Si≤0.10%, Mn: 0.35-0.60%, P≤0.005%, S≤0.008%, P+S≤0.012%, Ni: 3.0-3.75%, Fe: balance; Based on the total weight of the coating, the components of the coating are as follows in weight percentage: magnesite: 5-12%, calcite: 24-32%, barium carbonate: 2-4%, fluorite: 12-18%, barium fluoride: 3.0-5.0%, lithium fluoride: 1.0-3.0%, cerium fluoride: 0.4-1.2%, silicon micropowder: 3-10%, zircon sand: 0.6-2.5%, potassium cryolite: 1.0-3.0%, potassium glass powder 0.5-2.0%, low nitrogen nickel powder (N≤0.005%): 2.6-3.4%, low nitrogen molybdenum powder (N≤0.005%): 0.15-0.18%, manganese silicon alloy: 3-6%, ferroboron (B content 18-20%): 0.1-0.3%, magnesium powder: 0.5-1.2%, calcium alginate: 0.8-1.2%, potassium alginate: 0.4-0.6%, low titanium atomized iron powder (Ti≤0.005%): balance.
2. The welding rod for petrochemical cryogenic storage tank according to claim 1, characterized in that: The particle size of the potassium glass powder in the coating component is 200-300 meshes, and the particle size of the calcium alginate and potassium alginate is 100-200 meshes.
3. The welding rod for petrochemical cryogenic storage tank according to claim 1, characterized in that: Potassium-sodium mixed water glass with a modulus of 3.30 and a concentration of 35±1Be, which accounts for 15-30% of the total weight of the coating, is added, mixed with the coating, and evenly coated on the welding core, and then dried at a low temperature of 80-120°C for 3 hours and a high temperature of 350-420°C for 1 hour to prepare the petrochemical low-temperature storage tank welding rod.
4. The welding rod for petrochemical cryogenic storage tank according to any one of claims 1 to 3, characterized in that: The chemical composition of the deposited metal of the welding rod for petrochemical low-temperature storage tanks is as follows: C: 0.020-0.040%, Si: 0.15-0.25%, Mn: 0.50-0.80%, P: ≤0.008%, S: ≤0.008%, P+S≤0.015%, Ni: 3.30-3.70%, Mo: 0.06-0.08%, B: 0.0012-0.0018%, Mo / B=30-60, Ti: ≤0.001%, and the rest is Fe.
Citation Information
Patent Citations
Two-phase stainless steel electrode
CN102233489A
Low-temperature steel all-position welding rod for steel spherical tank welding and coating powder
CN105033502A
Low alloy steel welding electrode resistant to low-temperature impacts
CN106493486A
Low-temperature-resistant flux-cored wire for steel
CN109719427A
Special high-manganese welding rod for 25% Mn steel overhead welding
CN114193025A